Oriented Nanodomains: Vertical Orientation of Nanodomains on Versatile Substrates through Self‐Neutralization Induced by Star‐Shaped Block Copolymers (Adv. Funct. Mater. 34/2015). (September 2015) - Jang, Sangshin; Lee, Kyuseong; Moon, Hong Chul; Kwak, Jongheon; Park, Jicheol; Jeon, Gumhye; Lee, Won Bo; Kim, Jin Kon
Abstract : On page 5414 J.K. Kim and co‐workers use star‐shaped 18 arm poly(methyl methacrylate)‐block‐polystyrene copolymers to demonstrate that cylindrical and lamellar nanodomains can be vertically aligned on flexible substrates without the use of an additional layer to neutralize the preferential affinity between the substrate and each block. This method will contribute toward commercialization of direct self‐assembly for next‐generation integrated circuit and data storage media.